Acute Paraesophageal Hernia: Laparoscopic Repair With Adjunct T-Fastener Gastropexy for the High Operative Risk Patient. Issue 2 (April 2018) - Arevalo, Gabriel; Wilkerson, Jordan; Saxe, Jonathan
Abstract : Background: In the emergent setting, most paraesophageal hernia (PEH) repairs are done by laparotomy with adjunct gastropexy or gastrostomy tube (GT) placement. This adjunct to the repair can be performed expeditiously by a laparoscopic approach by utilizing T-fasteners. We present our case series of patients with PEHs and acute gastric volvulus that were managed with laparoscopy and how patient characteristics can influence the repair technique. Methods: Patients with high operative risk who underwent laparoscopic hiatal hernia repair with adjunct T-fastener gastropexy in the emergent setting between July 2014 and July 2016 were included in this study. Results: Thirteen patients underwent successful PEH repair and all were classified as urgent/emergent upon admission. In total, 30.7% were performed laparoscopically. The median patient age was 84 years. A laparoscopic GT or gastropexy was performed for fixation of the stomach. Crural closure by an anterior cruroplasty was performed in all patients. There were no mortalities. One patient required conversion of gastropexy into a GT given symptoms of dysphagia. Prolonged length of stay was related to postdischarge institutionalization. All patients remained free of obstructive symptoms. Conclusions: Laparoscopic PEH repair with adjunct gastropexy or GT placement should be considered in emergent cases for elderly patients with predominately obstructive symptoms. Laparoscopy for PEH repair is challenging and requires technical skills. T-fastener gastropexy or GT placement is safe, simple, and obviates the need for intracorporeal suturing. It also may be used to improve physician comfort with laparoscopy and to expedite the repair in this high-risk population.